Caudal clonidine and bupivacaine for combined epidural and general anaesthesia in children - Motsch, Johann; Böttiger, Bernd W.; Bach, Alfons; Böhrer, Hubert; Skoberne, Thomas Leopold; Martin, Eike (Acta anaesthesiologica Scandinavica, 1997)
Background: Clonidine produces analgesia by actions on α2-ad-renoceptors and enhances both sensory and motor blockade from epidural injection of local anaesthetics. Low-dose clonidine has been used so far for caudal injection in children. Our aim was to study the perioperative effects of high-dose caudal clonidine when added to low concentration of bupivacaine for combined epidural and general anaesthesia in children. Methods: After induction of general anaesthesia caudal block was performed either with 1 ml kg-1 bupivacaine 0.175% with the addition of clonidine 5 μg kg-1 (n=20), or with 1 ml kg-1bupivacaine 0.175% (n=20). The intraoperative anaesthetic requirements, the perioperative haemodynamic effects, respiratory rate, sedation score, postoperative pain scores and side effects were assessed by a blinded observer. A patient-controlled analgesia system was used for postoperative pain relief. The quality of postoperative pain relief was assessed using Smiley's pain analogue scale. Results: Intraoperative haemodynamic responses did not differ between the groups. However, during emergence from general anaesthesia children in the clonidine group had significantly lower heart rates and blood pressures compared to children in the control group. In addition, heart rates and blood pressures were also lower in the clonidine group in the early postoperative period (P?< 0.05). Postoperative analgesia was significantly better in the clonidine group as evidenced by the total number of requests (3 vs 12, P< 0.05) and the total amount of tramadol (20.5 mg vs 72.8 mg, P < 0.05) administered. The duration of the caudal analgesia was significantly longer in the clonidine group (20.9±7.4 h vs 14.4±10.9 h, P< 0.05). Conclusion: Our results suggest that caudal clonidine 5 μg kg-1 enhances and prolongs caudal blockade with bupivacaine 0.175% in children. It also blocks sympathoadrenergic responses during emergence from anaesthesia. Sedation and cardiovascular effects are observed up to 3 h into the postoperative period.